2000
DOI: 10.7557/2.20.4.1517
|View full text |Cite
|
Sign up to set email alerts
|

Growth and body weight of free-range reindeer in western Alaska

Abstract: Total body weight of 9749 reindeer calves and 4798 adult reindeer were measured from 1984 to 1999 on the Seward Peninsula, western Alaska, USA. Growth rates of male and female calves, and annual growth patterns of adults were determined. Male calves grew faster than female calves. Reproductive females were lighter than non-reproductive females during summer but there was no effect of reproduction on average body weights the following winter. Adult males age 3-5 were heavier during summer than winter. Castrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
1
14
1
Order By: Relevance
“…moose Alces alces; Cederlund et al 1991; roe deer; Capreolus capreolus; Gaillard et al 1996;red deer Cervus elaphus;Loison et al 1999b), and having higher absolute growth than females (see, e.g., Finstad and Prichard 2000), we found no evidence that climate influenced differently calf weight (autumn and early winter) and growth of males and females. Our results are in disagreement with the expectation that males in polygynous and highly dimorphic ungulates are more sensitive to harsh environmental conditions than females (e.g.…”
Section: Discussioncontrasting
confidence: 46%
“…moose Alces alces; Cederlund et al 1991; roe deer; Capreolus capreolus; Gaillard et al 1996;red deer Cervus elaphus;Loison et al 1999b), and having higher absolute growth than females (see, e.g., Finstad and Prichard 2000), we found no evidence that climate influenced differently calf weight (autumn and early winter) and growth of males and females. Our results are in disagreement with the expectation that males in polygynous and highly dimorphic ungulates are more sensitive to harsh environmental conditions than females (e.g.…”
Section: Discussioncontrasting
confidence: 46%
“…Indigenous caribou (Rangifer tarandus grantii) were not present on the Seward Peninsula in significant numbers at the time of this study to graze competitively with reindeer. Although growth and body weights of calves and adults were comparatively high across the Seward Peninsula there were differences among discrete populations of reindeer that are likely related to variation in forage quality (protein) during spring and summer (Finstad and Prichard, 2000;Finstad, 2008). Recent studies have also demonstrated the importance of diet in influencing protein allocation, protein balance, and reproduction in Rangifer (Barboza and Parker, 2008;Parker et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, proper seasonal placement of reindeer on a highly heterogeneous nutritional landscape is very critical for animal productivity (Klein, 1970;Pulliainen, 1971;Skogland, 1978;Staaland and Saebö , 1993;Finstad, 2008) Domestic reindeer were introduced to the Seward Peninsula; Alaska, during the late 1890s and currently are one of the primary livestock under production in Alaska (Stern et al, 1980;Finstad et al, 2006). Reindeer on the Seward Peninsula exhibit fast growth rates (0.43 kg day 21 for male, 0.37 kg day 21 for female calves) during summer and achieve a high body mass (98 kg for females in winter) and high reproductive rates (up to 39% yearling females lactating) compared to other circumpolar Rangifer populations (Prichard et al, 1999;Finstad and Prichard, 2000). Forage availability (energy) is often considered the primary constraint of production for free-ranging ungulates, but this may not be the case for reindeer on the Seward Peninsula.…”
Section: Introductionmentioning
confidence: 99%
“…Reindeer body weight varies considerably throughout the year due to the availability of food sources, their reproductive behavior pattern, and other environmental factors such as insect pests. In a 15-year study of reindeer on the Seward Peninsula, body weight of adult reindeer aged 4 years and older ranged between 165-230 lb (74.84-104.33 kg) for cows and 220-290 lb (99.79-131.54 kg) for bulls, depending on the season (Finstad & Prichard, 2000). Unpublished data collected by Finstad and colleagues show that adult females measure around 40 in (101.6 cm) at the top of the shoulder, while adult males measure around 48 in (121.92 cm).…”
Section: Figure 1 Alaska and The Seward Peninsulamentioning
confidence: 99%